2015
DOI: 10.1007/s00520-015-2970-8
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy cut-points in older people with cancer: how many medications are too many?

Abstract: Our results suggest that no single polypharmacy cut-point is optimal for predicting multiple adverse events in older people with cancer. In this population, the common definition of five-or-more-medications is reasonable for identifying 'at-risk' patients for medication review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 43 publications
2
79
0
Order By: Relevance
“…They also found that taking greater than 6.5 medications correlated with reduced performance status and frailty. This study did not evaluate PIMs or specific medication classes [17]. Studies involving a clinical intervention for PP/PIMs are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that taking greater than 6.5 medications correlated with reduced performance status and frailty. This study did not evaluate PIMs or specific medication classes [17]. Studies involving a clinical intervention for PP/PIMs are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…12 Taking 5 or more regular medications has been associated with falls, disability, and frailty in general geriatric populations and in geriatric oncology, and thus has some justification as a reasonable cut-point for polypharmacy based on the association with adverse outcomes in older patients. 13, 14 For example, the sensitivity and specificity for 5 or more medications and the risk of falls is 75.7% and 44.5%, respectively; at a cut-point of 10 or more medications, the sensitivity is 24.3% and specificity is 85.5%. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Around 20% of patients take 10 or more drugs and 10%-30% experience an adverse drug event in the course of a year. In around 4%, there is a life-threatening drug-drug interaction 26 . Altered physiology and drug handling, cormorbidities and co-medications (which frequently include non-prescription and herbal agents) interact to affect pharmacokinetics and pharmacodynamics.…”
Section: De-escalation Options For Elderly Patientsmentioning
confidence: 99%